Phase 1 trial of nelfinavir added to standard cisplatin chemotherapy with concurrent pelvic radiation for locally advanced cervical cancer. Issue 13 (1st May 2021) - Garcia‐Soto, Arlene E.; McKenzie, Nathalie D.; Whicker, Margaret E.; Pearson, Joseph M.; Jimenez, Edward A.; Portelance, Lorraine; Hu, Jennifer J.; Lucci, Joseph A.; Qureshi, Rehman; Kossenkov, Andrew; Schwartz, Lauren; Mills, Gordon B.; et al.
Abstract : Background: Nelfinavir (NFV), an HIV‐1 protease inhibitor, has been shown to sensitize cancer cells to chemoradiation (CRT). The objectives of this phase 1 trial were to evaluate safety and identify the recommended phase 2 dose of NFV added to concurrent CRT for locally advanced cervical cancer. Methods: Two dose levels of NFV were evaluated: 875 mg orally twice daily (dose level 1 [DL1]) and 1250 mg twice daily (DL2). NFV was initiated 7 days before CRT and continued through CRT completion. Toxicity, radiographic responses, and pathologic responses were evaluated. Serial tumor biopsies (baseline, after NFV monotherapy, on NFV + CRT, and posttreatment) were evaluated by immunohistochemistry, NanoString, and reverse‐phase‐protein‐array analyses. Results: NFV sensitized cervical cancer cells to radiation, increasing apoptosis and tumor suppression in vivo. Patients (n = 13) with International Federation of Gynecology and Obstetrics stage IIA through IVA squamous cell cervical carcinoma were enrolled, including 7 patients at DL1 and 6 patients at DL2. At DL1, expansion to 6 patients was required after a patient developed a dose‐limiting toxicity, whereas no dose‐limiting toxicities occurred at DL2. Therefore, DL2 was established as the recommended phase 2 dose. All patients at DL2 completed CRT, and 1 of 6 experienced grade 3 or 4 anemia, nausea, and diarrhea. One recurrence was noted at DL2, with disease outside the radiation field. Ten of 11 evaluable patients remained without evidence of disease at a median follow‐up of 50 months. NFV significantly decreased phosphorylated Akt levels in tumors. Cell cycle and cancer pathways also were reduced by NFV and CRT. Conclusions: NFV with CRT is well tolerated. The response rate is promising compared with historic controls in this patient population and warrants further investigation. Abstract : In a phase 1 clinical trial, nelfinavir, an HIV protease inhibitor, was determined to be safe and tolerable when added to standard chemoradiation therapy for locally advanced cervical cancer. Cervical tumor pAkt and pS6 protein levels decrease with nelfinavir treatment, and cell cycle and cancer‐associated pathways are further reduced with nelfinavir added to chemoradiation.